Role of periostin in inflammatory bowel disease development and synergistic effects mediated by the CCL5–CCR5 axis - Mukanova, Saida; Borissenko, Anton; Kim, Alexey; Bolatbek, Aigerim; Abdrakhmanova, Ainur; Vangelista, Luca; Sonnenberg-Riethmacher, Eva; Riethmacher, Dieter (Frontiers in Immunology, 2022)
Inflammatory Bowel Disease (IBD), comprising mainly Crohn’s Disease (CD) and Ulcerative Colitis (UC), is a chronic inflammatory disease of the gastrointestinal tract. In recent years, a wealth of data has been accumulated demonstrating the complex interplay of many different factors in the pathogenesis of IBD. Among these, are factors impacting on the epithelial barrier function, including vessel and extracellular matrix (ECM) formation, the gut microbiome (e.g., bacterial antigens) and, most importantly, the production of cytokines (pro- and anti-inflammatory) directly shaping the immune response. Patients failing to resolve the acute intestinal inflammation develop a chronic inflammation. It has been shown that the expression of the matricellular protein periostin is enhanced during IBD and is one of the drivers of this disease. The C-C chemokine receptor 5 (CCR5) is engaged by the chemotactic mediators CCL3/MIP-1α, CCL4/MIP-1β and CCL5/RANTES. CCR5 blockade has been reported to ameliorate inflammation in a murine IBD model. Thus periostin and CCR5 both are involved in the development of IBD. In this study, we investigated a potential cross-talk between the two signaling systems and tested a highly potent CCL5 derivative acting as CCR5-antagonist in a murine model of IBD. We observed that absence of periostin has an influence on the CCR5-expressing cell population of the gut. Our data further support the notion that targeted modulation of the periostin and CCR5 signaling systems bears therapeutic potential for IBD.